Delayed Rectifier Currents in Rat Globus Pallidus Neurons Are Attributable to Kv2.1 and Kv3.1/3.2 K(+) Channels - Baranauskas, Gytis (J Neurosci, 1999)
The symptoms of Parkinson disease are thought to result in part from increased burst activity in globus pallidus neurons. To gain a better understanding of the factors governing this activity, we studied delayed rectifier K(+) conductances in acutely isolated rat globus pallidus (GP) neurons, using whole-cell voltage-clamp and single-cell RT-PCR techniques. From a holding potential of −40 mV, depolarizing voltage steps in identified GP neurons evoked slowly inactivating K(+) currents. Analysis of the tail currents revealed rapidly and slowly deactivating currents of similar amplitude. The fast component of the current deactivated with a time constant of 11.1 ± 0.8 msec at −40 mV and was blocked by micromolar concentrations of 4-AP and TEA (K(D) ∼140 μm). The slow component of the current deactivated with a time constant of 89 ± 10 msec at −40 mV and was less sensitive to TEA (K(D) = 0.8 mm) and 4-AP (K(D) ∼6 mm). Organic antagonists of Kv1 family channels had little or no effect on somatic currents. These properties are consistent with the hypothesis that the rapidly deactivating current is attributable to Kv3.1/3.2 channels and the slowly deactivating current to Kv2.1-containing channels. Semiquantitative single-cell RT-PCR analysis of Kv3 and Kv2 family mRNAs supported this conclusion. An alteration in the balance of these two channel types could underlie the emergence of burst firing after dopamine-depleting lesions.